Does Research Training During Residency Promote Scholarship and Influence Career Choice? A Cross-Sectional Analysis of a 10-Year Cohort of the UCSF–PRIME Internal Medicine Residency Program. Issue 3 (2nd July 2016) - Kohlwes, Jeffrey; O'Brien, Bridget; Stanley, Marion; Grant, Ross; Shunk, Rebecca; Connor, Denise; Cornett, Patricia; Hollander, Harry
ABSTRACT: Problem : The Association of Program Directors in Internal Medicine, the Accreditation Council for Graduate Medical Education, the Alliance for Academic Internal Medicine, and the Carnegie Foundation report on medical education recommend creating individualized learning pathways during medical training so that learners can experience broader professional roles beyond patient care. Little data exist to support the success of these specialized pathways in graduate medical education. Intervention : We present the 10-year experience of the Primary Care Medicine Education (PRIME) track, a clinical-outcomes research pathway for internal medicine residents at the University of California San Francisco (UCSF). We hypothesized that participation in an individualized learning track, PRIME, would lead to a greater likelihood of publishing research from residency and accessing adequate career mentorship and would be influential on subsequent alumni careers. Context : We performed a cross-sectional survey of internal medicine residency alumni from UCSF who graduated in 2001 through 2010. We compared responses of PRIME and non-PRIME categorical alumni. We used Pearson's chi-square and Student's t test to compare PRIME and non-PRIME alumni on categorical and continuous variables. Outcome : Sixty-six percent (211/319) of alumni responded to the survey. A higher percentage of PRIME alumni published residency research projects compared to non-PRIME alumni (64% vs. 40%; p = .002). The number of PRIME alumni identifying research as their primary career role was not significantly different from non-PRIME internal medicine residency graduates (35% of PRIME vs. 29% non-PRIME). Process measures that could explain these findings include adequate access to mentors ( M 4.4 for PRIME vs. 3.6 for non-PRIME alumni, p < .001, on a 5-point Likert scale) and agreeing that mentoring relationships affected career choice ( M 4.2 for PRIME vs. 3.7 for categorical alumni, p = .001). Finally, 63% of PRIME alumni agreed that their research experience during residency influenced their subsequent career choice versus 46% of non-PRIME alumni ( p = .023). Lessons Learned : Our results support the concept that providing residents with an individualized learning pathway focusing on clinical outcomes research during residency enables them to successfully publish manuscripts and access mentorship, and may influence subsequent career choice. Implementation of individualized residency program tracks that nurture academic interests along with clinical skills can support career development within medicine residency programs.